Idiopathic Rotational Abnormalities of the Lower Extremities in Children and Adults. Issue 1 (January 2019) - Gruskay, Jordan A.; Fragomen, Austin T.; Rozbruch, S. Robert
Abstract : Rotational malalignment of the lower extremity is a potential cause of hip, knee, and ankle pain. Physical examination must include observation of gait and an assessment of femoral rotation and the thigh-foot axis with the patient prone. Advanced imaging helps to quantify the degree of deformity, improving the accuracy of the preoperative plan. Surgical correction of rotational malalignment of the femur and tibia is reserved for severe, symptomatic deformity. Future software that allows for 3-dimensional assessment of alignment and preoperative planning will further aid in the correction of the complex deformities.